Motivational techniques to increase 6th grade students´ oral proficiency at la moderna school during the school year 2015-2016 - Villanueva Barahona, Dionisio Damián (2015)
This project involves the application of motivational techniques in order to improve the oral proficiency in sixth graders from La Moderna Bilingual School. First of all, two class observations were conducted in order to evidence the research problem, and to determine the teacher´s academic performance in class.....